What Does AMH Tell Us in Pediatric Disorders of Sex Development? - Josso, Nathalie; Rey, Rodolfo A. (Frontiers in Endocrinology, 2020)
Disorders of sex development (DSD) are conditions where genetic, gonadal and/or internal/external genital sex are discordant. In many cases, serum testosterone determination is insufficient for the differential diagnosis. Anti-Müllerian hormone (AMH), a glycoprotein hormone produced in large amounts by immature testicular Sertoli cells, may be an extremely helpful parameter. In undervirilized 46,XY DSD, AMH is low in gonadal dysgenesis while it is normal or high in androgen insensitivity and androgen synthesis defects. Virilization of a 46,XX newborn indicates androgen action during fetal development, either from testicular tissue or from the adrenals or placenta. Recognizing congenital adrenal hyperplasia is usually quite easy, but other conditions may be more difficult to identify. In 46,XX newborns, serum AMH measurement can easily detect the existence of testicular tissue, leading to the diagnosis of ovotesticular DSD. In sex chromosomal DSD, where the gonads are more or less dysgenetic, AMH levels are indicative of the amount of functioning testicular tissue. Finally, in boys with a persistent Müllerian duct syndrome, undetectable or very low serum AMH suggests a mutation of the AMH gene, whereas normal AMH levels orient towards a mutation of the AMH receptor.